Legal Implications of Indonesia’s Amended Armed Forces Law for National Defense Capacity: Implikasi Hukum dari Perubahan Undang-Undang Tentara Nasional Indonesia terhadap Kapasitas Pertahanan Nasional - Erwin, Yanuar Putra; Silalahi, Wilma (Academia Open, 2026)
General Background: National defense capacity is a core legal concern amid increasingly complex conventional and non-conventional threats. Specific Background: The study examines Law Number 3 of 2025, which amends Law Number 34 of 2004 on the National Armed Forces, including changes concerning non-war military operations, civilian offices, retirement age, and coordination with defense authorities. Knowledge Gap: Legal debate remains over whether the revised framework can strengthen defense readiness while remaining aligned with constitutional principles, civilian supremacy, the rule of law, and human rights protection. Aims: This study analyzes the legal implications of the amended Armed Forces Law for national defense capacity and explains how constitutional legitimacy is shaped through formal and substantive judicial review before the Constitutional Court. Results: The findings show that the amended statute reinforces defense capacity through clearer institutional coordination, expanded non-war operations including cyber defense and overseas citizen protection, regulated access to certain civilian positions, and adjusted retirement provisions. Constitutional Court decisions rejected or did not accept formal and substantive challenges, confirming that the statute does not contradict the 1945 Constitution. Novelty: The study offers an integrated constitutional law reading of defense reform by linking amended military governance norms with judicial review outcomes and national defense capacity. Implications: The statute can function as a valid legal instrument for defense strengthening, provided that implementation remains subject to strict oversight, checks and balances, civilian supremacy, legality, and human rights safeguards. Highlights: Judicial review outcomes preserved the revised TNI framework. Non-war operational scope includes cyber defense and overseas citizen protection. Application requires strict oversight, civilian supremacy, legality, and human rights safeguards. Keywords: National Defense Forces, TNI Act, Indonesian National Armed Forces.